2013
DOI: 10.1080/0972060x.2013.831553
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils from Bolivia. XI. Verbenaceae :Aloysia gratissima(Gillies & Hook.) Tronc. and Boraginaceae :Cordia chacoensisChodat

Abstract: The compositions of the essential oil of the aerial parts of Aloysia gratissima and Cordia chacoensis are almost similar. In both cases, oxygenated sesquiterpenes constituted the main group (between 40 and 50 %): 6α-hydroxygermacra-1(10),4-diene being the major compound (~ 16 %). Sesquiterpenic molecules constitute the second important group (30 -34 %) with β-caryophyllene as the major compound (8.0 %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Within the Cordia genus , there is a certain variation in the predominance of certain components of essential oils. Some species mainly contain monoterpene hydrocarbons common to C. cylindrostachia [ 50 ], C. globosa [ 51 ]; some sesquiterpene hydrocarbons, as seen in C. verbenacea [ 6 ], C. leucocephala [ 52 ] and C. millenii [ 53 ]; a mixture of monoterpene hydrocarbons and sesquiterpenes prominent in C. trichotoma [ 54 ] and C. multispicata [ 55 ]; oils containing oxygenated monoterpenes/sesquiterpenes, such as C. myxa [ 56 ] and C. chacoensis [ 57 ], respectively; and oils with a high content of non-terpenes, present in C. sebestena [ 58 ] and C. gilletii [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the Cordia genus , there is a certain variation in the predominance of certain components of essential oils. Some species mainly contain monoterpene hydrocarbons common to C. cylindrostachia [ 50 ], C. globosa [ 51 ]; some sesquiterpene hydrocarbons, as seen in C. verbenacea [ 6 ], C. leucocephala [ 52 ] and C. millenii [ 53 ]; a mixture of monoterpene hydrocarbons and sesquiterpenes prominent in C. trichotoma [ 54 ] and C. multispicata [ 55 ]; oils containing oxygenated monoterpenes/sesquiterpenes, such as C. myxa [ 56 ] and C. chacoensis [ 57 ], respectively; and oils with a high content of non-terpenes, present in C. sebestena [ 58 ] and C. gilletii [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Essential oil a-Pinene C. curassavica [211] C. cylindrostachya [136] C. verbenacea [137,138] Leaves Twigs and Leaves Flower, Leaves a-Humulene C. globosa [51] C. verbenacea [106,139] Leaves a-Cadinol C. trichotoma [62] Wood a-Muurolol C. trichotoma [62] Wood 6a-Hydroxygermacra-1(10) 4-diene C. chacoensis [140] b-Caryophyllene C. boissieri [141,142] C. chacoensis [135,143] C. curassavica [41] C. globosa [144] C. leucocephala [135] C. leucomalloides [145] C. multispicata [138] C. verbenacea [106,139] Flower Leaves Flowers, Stem Aerial parts, Leaves b-Pinene C. curassavica [135] Leaves b-Eudesmol C. curassavica [146] Aerial parts b-Phellandrene C. multispicata [144] Leaves, flowers, Stem d-Cadinene C. leucomalloides [135] C. trichotoma [72] C. verbenacea [138] Leaves Wood Leaves Aromadendrene C. chacoensis [142] Alloaromadendrene C. verbenacea [137] Flower, leaves Bicyclogermacrene C. curassavica [135] C. globosa [41,143] C. leucocephala [135] C. leucomalloides [145] C. verbenacea [138] Leaves Aerial parts, Leaves Cadinene C. chacoensis [142] Camphene C. cylindrostachya [136] Twigs and leaves Elemol C. chacoensis [142] Germacrene D C. leucomalloides [135] C. ver...…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…exaltata [92] Bark Rufescenolide B (127) C. americana [97] Bark Rufescenolide C (128) C. americana [97] Bark Rufescenolide D (129) C. americana [97] Bark Yunnaneic acid I (130) C. americana [97] Bark Yunnaneic acid J (131) C. americana [97] Bark [61] Root bark Cordicilin (134) C. latifolia [77] Leaves Latifolicinin A (135) C. latifolia [98] Fruit Latifolicinin B (136) C. latifolia [98] Fruit Latifolicinin C (137) C. latifolia [98] Fruit Latifolicinin D (138) C. latifolia [98] Fruit 2.11. Phenolics 2-Hydroxy-3-(4-hydroxy-3-methoxyphenyl)-2-Me propionamide C. macleodii [128] Leaves and flower Methyl caffeate C. rufescens [123] Stem Methyl rosmarinate (139) C. dichotoma [101] C. rufescens [123] Leaves Stem Magnesium lithospermate (140) C. spinescens [135] Leaves Calcium rosmarinate (141) C. spinescens [135] Leaves Magnesium rosmarinate (142) C. spinescens [135] Leaves…”
Section: Abietane Diterpenesmentioning
confidence: 99%
“…The two above-cited studies were carried out in the Santa Maria city, Rio Grande do Sul (Brazil). Arze et al [ 16 ] identified the constituents sabinene, ß -pinene, and ß -caryophyllene in the essential oil of A. gratissima collected in the Cochabamba Province of Mizque (Bolivia). The essential oil of A. gratissima collected in the São Carlos city, São Paulo (Brazil), studied by Trovati et al [ 27 ], presents isopinocamphone (25.4%), limonene (15.1%), and guaiol (12.7%) as its major constituents.…”
Section: Resultsmentioning
confidence: 99%